EU Foreign Policy Instruments in the Eastern Partnership Countries: From Development Aid to Military Assistance - O. V. Shishkina (Vestnik MGIMO-Universiteta)
In 2022, the European Union (EU) took the unprecedented step of providing financial assistance for military purposes to a warring state, Ukraine, while also establishing mechanisms to incentivize member states to supply arms and military equipment to Kyiv. These measures, characterized as "hard instruments" of EU foreign policy, were developed in response to the "return of high-intensity warfare to Europe." This marked a significant departure from the EU’s traditional emphasis, particularly in the 2000s and 2010s, on non-military foreign policy tools. During that period, the EU took pride in achieving its objectives without recourse to force and deliberately avoided military pressure in international relations.This article explores the concept of foreign policy instruments, categorizing them into hard, soft, and hybrid tools. It examines the EU’s repertoire of foreign policy instruments, distinguishing between its long-standing approaches and those recently developed. Through an analysis of EU policy documents, the article identifies the Union’s evolving interests in the Eastern Partnership countries—Azerbaijan, Armenia, Belarus, Georgia, Moldova, and Ukraine—and evaluates the practical application of its tools in the region since the launch of the "Eastern Policy" (comprising the European Neighborhood Policy and the Eastern Partnership initiative).The study concludes by analyzing the use of soft, hard, and hybrid instruments in the Eastern Partnership, outlining the nature of the transformations in EU foreign policy and hypothesizing their underlying causes. These changes in the EU’s foreign policy toolkit reveal broader trends in its strategic development and shed light on the specific dynamics of its engagement with six post-Soviet countries, which remain strategically significant for the EU while occupying a critical space within Russia’s sphere of interests.